Long‐term clinical results of posterior chamber phakic intraocular lens implantation to correct myopia. (9th February 2016) - Lee, Jongsoo; Kim, Younghee; Park, Saekwang; Bae, Jungae; Lee, Seunguk; Park, Youngmin; Lee, Jonghun; Lee, Ji‐Eun
Abstract: Background: The aim of this study was to determine whether implantable collamer lens (ICL) implantation to correct myopia is an effective and safe surgical option even after long‐term follow up. Design: A retrospective observational study was carried out. Participants: A total of 281 eyes of 145 myopic patients were included in the study. Methods: Patients underwent ICL implantation and had the follow‐up period of at least 5 years (87 ± 18.9 months). Main Outcome Measures: Outcome measures included uncorrected and corrected distance visual acuities, refraction for the evaluation of efficacy, safety, stability and predictability, ICL vault and adverse events. Results: The final mean logMAR uncorrected and corrected distance visual acuities were 0.02 ± 0.19 and −0.12 ± 0.13, respectively. The mean efficacy and safety indices were 1.04 ± 0.32 and 1.20 ± 0.26. The mean spherical equivalent decreased from −8.74 ± 2.27 diopter (D) to −0.58 ± 0.72 D, and there was high predictability with 69.8% and 87.2% having a postoperative refraction within 0.5 D and 1.0 D, respectively. The mean postoperative vault was changed from 2.53 ± 0.6 to 2.00 ± 0.7. Six (2.1%) eyes developed cataract, and the mean endothelial cell loss was 7.8 ± 8.3%. Increased intraocular pressure was found in two (0.7%) eyes that required the exchange of lenses with different sizes. Conclusions: Implantable collamer lens implantation to correct myopia was an effective and safe surgery with high predictability and stability during long‐term follow up. Slight myopic shift and cataract formation related with change in vault should be further evaluated.